Chemometric characterization of three varietal olive oils (Cvs. cobrancosa, madural and verdeal Transmontana) extracted from olives with different maturation indices - Matos, Luís C. (2007)
This paper evaluates the usefulness of three chemical parameters (compositions on tocopherols, sterols and fatty acids) as a tool to discriminate three varietal olive oils (Cvs. Cobrançosa, Madural and Verdeal Transmontana), which are permitted cultivars for the production of ‘‘Trás-os-Montes olive oil’’, a Portuguese protected designation of origin (PDO) product. The olives were collected during the year crop 2000/2001 from the same orchard, in order to eliminate the geographical and climatic influences. Lots with different maturation indices were prepared to allow the evaluation of the ripening stage on the characteristics of varietal olive oils produced from each cultivar. Statistical methods such as multivariate analysis of variance (MANOVA), principal components analysis (PCA) and cluster analysis were used to evaluate significant differences on the studied parameters. Regarding the results, the three cultivars were clearly discriminated.